2017
DOI: 10.1111/jce.13152
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Modulation for the Treatment of Ventricular Arrhythmias: Therapeutic Use of Percutaneous Stellate Ganglion Blocks

Abstract: Ventricular tachycardia (VT), ventricular fibrillation (VF), and electrical storm are commonly encountered emergency conditions in cardiac and surgical intensive care units. In most cases, recurrent ventricular arrhythmias or electrical storm are associated with a heightened sympathetic tone. These arrhythmias can be difficult to treat and may be refractory to beta-blockade, antiarrhythmic therapy, sedation, and mechanical hemodynamic support. While monomorphic ventricular tachycardia and PVC-triggered polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…In patients requiring uninterrupted anticoagulation, such as those with high intracardiac thrombi burden or patients receiving extracorporeal membrane oxygenation, an alternative approach of percutaneous stellate ganglion block can be considered. However, only several case reports exist on its use in VT storm outside of the peri–myocardial infarction period …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients requiring uninterrupted anticoagulation, such as those with high intracardiac thrombi burden or patients receiving extracorporeal membrane oxygenation, an alternative approach of percutaneous stellate ganglion block can be considered. However, only several case reports exist on its use in VT storm outside of the peri–myocardial infarction period …”
Section: Discussionmentioning
confidence: 99%
“…However, only several case reports exist on its use in VT storm outside of the peri-myocardial infarction period. 9,35 TEA Response as Predictor of Response to CSD Similar to stellate ganglion block, 23 the ability for TEA response to predict CSD response is poor: in combination with patients included in the study by Bourke et al, 18 2 patients had a complete response to TEA but no response to left CSD, 1 patient had no response to TEA but a complete response to bilateral CSD, and 2 patients had a compete response to TEA and had a partial or complete response to left CSD (1 each). This discrepancy in response between the 2 procedures may reflect the different degrees of autonomic modulation provided by each: sympathetic blockade with TEA occurs more centrally from that of the bilateral stellate ganglia and affects both stellate ganglia; left CSD alone may not be as effective.…”
Section: Anticoagulation With Teamentioning
confidence: 99%
“…Jonnesco first performed successful cardiac autonomic modulation by left stellectomy for treatment of severe angina pectoris and ventricular arrhythmias in 1920 . Since then there have been few case reports and small single‐center studies published in literature . We previously reported that left SGB and bilateral CSD are effective in treating ventricular arrhythmias in patients with refractory multivessel coronary artery spasm .…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of neuromodulation include pharmacologic beta-adrenergic receptor blockade, thoracic epidural anesthesia (TEA) spinal cord stimulation (SCS), and stellate ganglion block (SGB) (5). Stellate ganglion block (SGB) is performed by injecting local anesthetic agents percutaneously to stellate ganglion, which is less invasive than CSD and can be performed at bedside in emergent setting in patients with hemodynamic instability Currently, besides case reports and small series, limited evidence is available regarding the role of SGB in ES (1537). To better understand the role of SGB in ES (particularly to address patient characteristics, techniques, and overall efficacy of SGB), we performed dedicated literature searches and performed this systemic review.…”
Section: Introductionmentioning
confidence: 99%